Autodrive Land Vehicle Control by Using PID - I. Swadexi; U. Rudi; N. Heriansyah (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Institut Teknologi Sumatera, Lampung Selatan, Lampung, Indonesia, 2019)
In towards industry 4.0, the autodrive vehicle is needed to give people relaxed driving. There are many research in autodrive vehicle such as waymo-the Google driving car project and Tesla Self Driving Autopilot. In This paper is presented about Autodrive Land Vehicle (ALV) control by using PID. The autodrive Land vehicle can drive autonomously by using GPS Information such as Latitude and longitude to navigate in an area. The vehicle is controled to follow the given waypoint that set by operator on ground control station. PID control is used to control steering of the vehicle’s front wheel and to control the heading of the vehicle. From the Implementation result, it is obtained that the vehicle could track the given waypoint with small error.